Acute hyperglycaemia prevents the protective effect of pre-infarction angina on microvascular function after primary angioplasty for acute myocardial infarction. Issue 11 (1st April 2008) - Takahashi, T; Hiasa, Y; Ohara, Y; Miyazaki, S; Mahara, K; Ogura, R; Miyajima, H; Yuba, K; Suzuki, N; Hosokawa, S; Kishi, K; Ohtani, R
Abstract : Background: Acute hyperglycaemia has been associated with impaired microvascular function after acute myocardial infarction (AMI), whereas pre-infarction angina (PIA) occurring shortly before the onset of AMI has been shown to reduce microvascular injury after reperfusion. Objective: To examine whether acute hyperglycaemia prevents the protective effect of PIA on microvascular function after AMI. Methods: We studied 205 patients with a first anterior wall AMI who underwent primary angioplasty within 12 hours of onset. Coronary flow velocity parameters were assessed immediately after reperfusion using a Doppler guidewire. Severe microvascular injury was defined as the presence of systolic flow reversal and diastolic deceleration time <600 ms. Echocardiographic wall motion was analysed before revascularisation and 4 weeks later. Results: Acute hyperglycaemia, defined as a blood glucose level of ⩾198 mg/dl on admission, was found in 67 (33%) patients. In patients without acute hyperglycaemia, PIA was associated with a lower incidence of systolic flow reversal, a longer diastolic deceleration time and a higher coronary flow reserve. However, in patients with acute hyperglycaemia there was no significant difference in these same parameters between patients with and without PIA. In the presence of acute hyperglycaemia PIA did not improve the change in wall motion score. In a multivariate model, the absence of PIA was an independent determinant of severe microvascular injury in patients without acute hyperglycaemia (odds ratio 6.28, p = 0.001), but not in patients with acute hyperglycaemia. Conclusion: The protective effect of PIA on microvascular function was attenuated in patients with acute hyperglycaemia, resulting in unfavourable functional recovery.